The future of incentives as a lever to increase HIV testing in the workplace : evidence from a field experiment - Weihs, Martin Erich (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MPhil (Industrial Psychology. Africa Centre for HIV/AIDS Management))--University of Stellenbosch, 2010.